2022
DOI: 10.5888/pcd19.210315
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Clinician Recommendations for Colorectal Cancer Screening Among Average-Risk Patients: Data From a National Survey

Abstract: What is already known on this topic?Colorectal cancer (CRC) screening among average-risk patients is underused in the US. Clinician recommendation is strongly associated with screening completion.What is added by this report?We examined clinicians' routine recommendations of 7 guidelinerecommended screening methods and factors associated with these recommendations.What are the implications for public health practice?A sizable portion of clinicians reported guideline-discordant screening intervals and age to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Colonoscopies were the most recommended modality, while stool-based tests made up less than a quarter of recommended tests, and few adults reported being recommended multiple modalities. This is consistent with prior research that has shown healthcare professionals prefer colonoscopies due to preference for visual inspection and concern regarding the sensitivity/specificity of stool-based tests ( Finney Rutten et al, 2022 , Zhu et al, 2022 ). However, it is important to incorporate patient preferences into CRC recommendations as adults who are given a choice of modalities have higher rates of screening completion ( Inadomi et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Colonoscopies were the most recommended modality, while stool-based tests made up less than a quarter of recommended tests, and few adults reported being recommended multiple modalities. This is consistent with prior research that has shown healthcare professionals prefer colonoscopies due to preference for visual inspection and concern regarding the sensitivity/specificity of stool-based tests ( Finney Rutten et al, 2022 , Zhu et al, 2022 ). However, it is important to incorporate patient preferences into CRC recommendations as adults who are given a choice of modalities have higher rates of screening completion ( Inadomi et al, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…About 37% of patients preferred colonoscopy, compared to 31% and 9% who preferred blood stool test and sigmoidoscopy, respectively. Further educational interventions are needed to provide clinicians with complete understanding of the CRC screening process, including up-to-date guidelines for recommended screening modalities and consideration of patient, clinician, and health system factors that may impact the effectiveness of each method [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the American College of Gastroenterology (ACG) recommended CRC screening in average-risk individuals between the ages of 45 and 75 [ 7 , 8 ]. There are several CRC screening modalities currently available including blood stool tests, sigmoidoscopy, and colonoscopy [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%